Percutaneous transhepatic cholangioscopy for indeterminate biliary strictures using the SpyGlass system: a case series - Du, Lillian; D’Souza, Pernilla; Thiesen, Aducio; Girgis, Safwat; Owen, Richard; McNally, Dermot; Sarlieve, Philippe; Sandha, Gurpal (Endoscopy, 2015)
Peroral cholangioscopy is useful in differentiating benign from malignant biliary strictures. However, when conventional biliary access via endoscopic retrograde cholangiopancreatography (ERCP) fails, percutaneous transhepatic cholangioscopy (PTCS) via the SpyGlass cholangioscopy system can be used to achieve a diagnosis. Four patients with biliary strictures in whom conventional ERCP was not possible and percutaneous brushings were either nondiagnostic or unsatisfactory were investigated with PTCS. The technique of PTCS involves insertion of the SpyGlass cholangioscope through a percutaneous transhepatic sheath, placed just prior to the procedure, to visualize the stricture and obtain biopsies with the SpyBite forceps. On the basis of our early observations, we conclude that PTCS using the SpyGlass cholangioscopy system for the assessment of biliary strictures is feasible, safe, and provides high diagnostic accuracy.